2013
DOI: 10.1515/zgl-2013-0024
|View full text |Cite
|
Sign up to set email alerts
|

Kategorien der Redewiedergabe im Deutschen: Konjunktiv I versus sollen

Abstract: In present-day German, the present subjunctive (Konjunktiv I) and the modal verb sollen 'shall' are used to mark reported discourse. In this paper, we aim at clarifying the semantic relationship between these two markers. We suggest that they basically pertain to two separate semantic-functional domains, viz. origoshifting versus evidentiality. While Konjunktiv I is an origo-shifting quotative marker, sollen is a reportive evidential marker. We argue that the proposed basic difference in semantics accounts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
1
2
0
1
Order By: Relevance
“…In his investigation of the semantics of reportative sollen in complement clauses, Schenner (2008Schenner ( , 2010 identifies three readings that sollen can adopt in this syntactic context: Although Schenner (2008Schenner ( , 2010 adopts these categories to examine the semantics of sollen in complement clauses, I find it useful to extend them to the investigation of the readings of sollen in other syntactic contexts as well, including main, adverbial, and attributive clauses. My analysis of the corpus data suggests that the concord reading, in which sollen signifies 'p' rather than 'it is reported that p', can be triggered not only when sollen is embedded under a speech report predicate, as noted by Schenner (2008Schenner ( , 2010, Diewald/Smirnova (2013) and Socka (2013), but in all cases where another marker of reporting is present, confirming what was stated in Schenner (2007: 210). This element can be a superordinate reporting clause, a parenthetical reporting clause, or the mention of an information source in the form of a prepositional phrase.…”
Section: Syntactic Contexts and Readings Of Reportative Sollensupporting
confidence: 73%
See 2 more Smart Citations
“…In his investigation of the semantics of reportative sollen in complement clauses, Schenner (2008Schenner ( , 2010 identifies three readings that sollen can adopt in this syntactic context: Although Schenner (2008Schenner ( , 2010 adopts these categories to examine the semantics of sollen in complement clauses, I find it useful to extend them to the investigation of the readings of sollen in other syntactic contexts as well, including main, adverbial, and attributive clauses. My analysis of the corpus data suggests that the concord reading, in which sollen signifies 'p' rather than 'it is reported that p', can be triggered not only when sollen is embedded under a speech report predicate, as noted by Schenner (2008Schenner ( , 2010, Diewald/Smirnova (2013) and Socka (2013), but in all cases where another marker of reporting is present, confirming what was stated in Schenner (2007: 210). This element can be a superordinate reporting clause, a parenthetical reporting clause, or the mention of an information source in the form of a prepositional phrase.…”
Section: Syntactic Contexts and Readings Of Reportative Sollensupporting
confidence: 73%
“…The global reading in (10).b would be appropriate if the letters reported a fact. This ambiguity can be observed in the historical newspapers analyzed in this study and in contemporary ones (Schenner 2008(Schenner : 559-560, 2010Smirnova/Diewald 2013: 459, Socka 2013.…”
Section: Syntactic Contexts and Readings Of Reportative Sollenmentioning
confidence: 73%
See 1 more Smart Citation
“…64 À ce propos, cf. aussi Smirnova & Diewald (2013). 65 De telles descriptions scalaires se trouvent dans Buscha (1984 : 215), Buscha et al (1985 : 21), Öhlschläger (1989 : 206), Raynaud (1975 : 87), Tarvainen (1976: 22), Vater (1975 ou encore Wunderlich (1981 : 39) ; similairement, Gerstenkorn (1976 : 354-355) s'interroge sur les degrés de probabilité pouvant être associés aux verbes modaux au moyen d'un questionnaire visant l'assimilation de ces formes avec des adverbes (modaux).…”
Section: Sémantique Des Verbes Modaux Allemandsunclassified